LEMBAGA PENDIDIKAN DAN KADERISASI DA’I: Studi Kasus pada Lembaga Pendidikan Hidayatullah di Kudus - MOH ROSYID (Universitas Islam Negeri (UIN) Mataram, 2019)
This research aims at understanding dakwah of Hidayatullah by educational institution in Kudus. Data of this paper are gathered through interview and observation which then analyzed in descriptive qualitative method. Al-Aqsha Hidayatullah Foundation is unique for its combination of formal education and pesantren in order to strengthen character building of the students’ trough learning to recite Quran regularly, tajwid, daily prayers both obligatory and additional one. Thus, to what extend does this method succeed in building the character of students and religious tolerance? Hidayatullah Foundation is often perceived to disseminate intolerance among its members due to its members’ outward appearance such as clothes, bearded, and dark forehead.